Argumentieren mit dem Praxisschock Einordnungen und Funktionen - Keitel, Juliane (Per EduArt. Kunstpädagogische Materialien für Studium und Schule, 2023)
Praxisschock (practice shock) was and is often used in reference to the career entry into a school teaching profession. This article examines the semantic field opened up by the term and the problems specific to the teaching profession to which it (does not) draw attention in its metaphor. In the further course, crisis-like career entry phenomena are negotiated as experiences of difference specific to the teaching profession and related to the antinomic structure of the professional field. On the basis of interview material, various functions are elaborated that identify the rhetorical use of practice shock as a strategic one. Based on the analysed functions and in the context of what a teacher training programme can and should achieve, the question of how talk of practice shock could become productive in academic teaching is examined.